DRIVING FACTORS FOREIGN DIRECT INVESTMENT IN 5 ASEAN COUNTRIES (MALAYSIA,THAILAND, SINGAPORE,INDONESIA AND VIETNAM) - Eka Septiani A. Dadu; Boby Rantow Payu (European Journal of Research Development and Sustainability, 2022)
The results of the study show that from 1990-2019 (1) Inflation has a positive and significant effect on FDI in Indonesia, Thailand and Vietnam. Meanwhile, in Malaysia, inflation has a positive but not significant effect on FDI. In Singapore, inflation has a negative but not significant effect on FDI. (2) Interest rates have a negative and significant effect on FDI in Vietnam, while in Indonesia, Malaysia and Singapore interest rates have a negative but not significant effect on FDI, in Thailand interest rates are positive but not significant on FDI. (3) Exchange rate has a negative and significant effect on FDI in Indonesia, Malaysia and Vietnam. Meanwhile, Thailand has a positive and significant impact. In Singapore, the exchange rate on FDI has a positive but not significant effect. (4) Wages on FDI in Malaysia and Singapore have a negative and significant effect, while Indonesia has a positive and significant effect. In Thailand and Vietnam, wages have a positive but not significant effect on FDI. (5) Income per capita on FDI in Singapore, Thailand and Vietnam has a positive and significant effect. Meanwhile, Indonesia and Malaysia the effect was negative but not significant